1978
DOI: 10.1051/jphys:0197800390100112500
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties and instability phenomena in doped Euo

Abstract: Résumé. 2014 Nous avons étudié l'influence de la concentration de porteurs libres sur les propriétés magnétiques de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
12
1

Year Published

1979
1979
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 13 publications
4
12
1
Order By: Relevance
“…The data shown in Fig. 1 are comparable to the data published by Mauger et al 31 This is one of the indications that our samples are consistent with those of other authors, though coming from different sources at different times. Other such signs of consistency among samples will come from NMR data, as shown below.…”
Section: Magnetization Vs Temperaturesupporting
confidence: 92%
See 1 more Smart Citation
“…The data shown in Fig. 1 are comparable to the data published by Mauger et al 31 This is one of the indications that our samples are consistent with those of other authors, though coming from different sources at different times. Other such signs of consistency among samples will come from NMR data, as shown below.…”
Section: Magnetization Vs Temperaturesupporting
confidence: 92%
“…We observed an abrupt increase of the amplitude of the exchange interaction with doping. This is consistent with the dependence on Gd concentration of the Curie temperature for which different theoretical explanations have been proposed by Mauger et al, 31,59 Nolting and Oleś, 60 We discovered that the lineshape of the Eu resonance in Gd doped EuO was broader than in pure EuO and that the broadening increases abruptly with Gd concentration. We also observed that the broadening increases with increasing temperature.…”
Section: Exchange Integral J Vs Dopingsupporting
confidence: 91%
“…7 is that the maximum value for T C with Gd doping is 125 K. We cannot reproduce the higher values (e.g., 130-170 K) reported in the literature. 7,8,9,10,12,13,14,15,18 It was inferred that stoichiometry problems could add to an extra increase in T C . 5,11 In this respect it is interesting to note that indeed oxygen deficiencies in Gd-free EuO samples already lead to enhancements of T C up to 140-150 K. 17,19,20 In our case we can exclude the presence of oxygen vacancies: the samples all were grown under Eu-distillation conditions, and under these conditions we have observed for the pure EuO films that they have the bulk T C value of 69 K and that they remain semiconducting and are, in fact, extremely insulating down to the lowest temperatures.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…The interaction between the Eu f-electrons and the dopant electrons enhances the ferromagnetic exchange energy 4,5 and results in an increased T C . To date, this has been accomplished through the use of trivalent cations including iron, [6][7][8] lanthanum, 1,9,10 gadolinium, [11][12][13][14][15][16][17] and holmium. 9 Alternatively, the T C can be increased by deliberately making oxygen-deficient EuO such that the resulting oxygen vacancies donate an electron.…”
mentioning
confidence: 99%